Semiotika dalam website olympics.com: komunikasi tim campuran panahan korea selatan di olimpiade tokyo 2020 (Jurnal Kajian Media, 2023)
The success of each athlete in obtaining peak performance during competition depends on the players' and coaches' ability to communicate. When participating in practices and games, communication is crucial and cannot be neglected. In both individual and team events during archery competitions, communication becomes more and more intense. This study looked at how the South Korean archery team's athletes and coaches communicated during the 2020 Tokyo Olympics. Using semiotics (Peirce), South Korean archery teams' performances in the finals of two competitions (mixed team and men/women team) were examined. The results of this research showed that communication between the archers and their coaches was dominated by non-verbal communication in mixed team’s numbers symbolised by the high five.